Edge Effects on Community and Social Structure of Northern Temperate Deciduous Forest Ants. (22nd August 2012) - Banschbach, Valerie S.; Yeamans, Rebecca; Brunelle, Ann; Gulka, Annie; Holmes, Margaret
Abstract : Determining how ant communities are impacted by challenges from habitat fragmentation, such as edge effects, will help us understand how ants may be used as a bioindicator taxon. To assess the impacts of edge effects upon the ant community in a northern temperate deciduous forest, we studied edge and interior sites in Jericho, VT, USA. The edges we focused upon were created by recreational trails. We censused the ants at these sites for two consecutive growing seasons using pitfall traps and litter plot excavations. We also collected nests of the most common ant species at our study sites, Aphaenogaster rudis, for study of colony demography. Significantly greater total numbers of ants and ant nests were found in the edge sites compared to the interior sites but rarefaction analysis showed no significant difference in species richness. Aphaenogaster rudis was the numerically dominant ant in the habitats sampled but had a greater relative abundance in the interior sites than in the edge sites both in pitfall and litter plot data. Queen number of A. rudis significantly differed between the nests collected in the edge versus the interior sites. Habitat-dependent changes in social structure of ants represent another possible indicator of ecosystem health.